Mrs. Lincoln's dressmaker: a novel (Thorndike Press large print basic, ,, 2013)
New York Times bestselling author Jennifer Chiaverini illuminates the extraordinary friendship between Mary Todd Lincoln and Elizabeth Hobbs Keckley, a former slave who won her freedom by the skill of her needle, and the friendship of the First Lady by her devotion. In Mrs. Lincoln’s Dressmaker, novelist Jennifer Chiaverini presents a stunning account of the friendship that blossomed between Mary Todd Lincoln and her seamstress, Elizabeth “Lizzie” Keckley, a former slave who gained her professional reputation in Washington, D.C. by outfitting the city’s elite. Keckley made history by sewing for First Lady Mary Todd Lincoln within the White House, a trusted witness to many private moments between the President and his wife, two of the most compelling figures in American history. In March 1861, Mrs. Lincoln chose Keckley from among a number of applicants to be her personal “modiste,” responsible not only for creating the First Lady’s gowns, but also for dressing Mrs. Lincoln in the beautiful attire Keckley had fashioned. The relationship between the two women quickly evolved, as Keckley was drawn into the intimate life of the Lincoln family, supporting Mary Todd Lincoln in the loss of first her son, and then her husband to the assassination that stunned the nation and the world. Keckley saved scraps from the dozens of gowns she made for Mrs. Lincoln, eventually piecing together a tribute known as the Mary Todd Lincoln Quilt. She also saved memories, which she fashioned into a book,Behind the Scenes: Thirty Years a Slave and Four Years in the White House. Upon its publication, Keckley’s memoir created a scandal that compelled Mary Todd Lincoln to sever all ties with her, but in the decades since, Keckley’s story has languished in the archives. In this impeccably researched, engrossing novel, Chiaverini brings history to life in rich, moving style.